Technology-enabled social-emotional learning for University educators: a systematic review - Mukhemar, Razan; Affouneh, Saida; Burgos, Daniel (Frontiers in Education, 2025)
IntroductionSocial-emotional learning (SEL) has gained increasing attention in higher education as a critical set of competencies for both educators and students. While SEL frameworks are well established in K–12 contexts, less is known about technology-enabled SEL interventions targeting university educators across diverse and cross-cultural settings.MethodsThis systematic review followed PRISMA guidelines and synthesized empirical evidence from five academic databases (ERIC, ScienceDirect, JSTOR, EBSCOhost, and SpringerLink). Comprehensive search strategies combined terms related to SEL, higher education, technology, and cross-cultural adaptability. Out of 2,296 initial records, 896 duplicates were removed, and 1,400 records underwent title and abstract screening. After excluding 1,135 studies, 265 full-text articles were assessed for eligibility, resulting in 22 studies included in the final synthesis.ResultsThematic analysis revealed three central domains: (1) development of SEL competencies such as emotional regulation, self-awareness, and responsible decision-making; (2) integration of digital tools including online platforms, virtual simulations, and mobile applications; and (3) adaptation to cultural diversity and educator readiness in global higher education contexts.DiscussionFindings highlight the potential of technology to foster SEL among university educators while also underscoring persistent challenges related to scalability, long-term effectiveness, and cultural responsiveness. The review provides evidence to guide the development of a cross-culturally adaptable SEL toolkit to support faculty professional development in increasingly globalized higher education systems.